MicroRNA‐9 exerts antitumor effects on hepatocellular carcinoma progression by targeting HMGA2 - Xiangang Xu; Haibo Zou; Lanyun Luo; Xiankui Wang; Guan Wang (FEBS Open Bio, 2019)
Accumulating evidence has demonstrated that the aberrant expression of microRNAs (miRs or miRNAs) may contribute to the initiation and progression of various types of human cancer and may also constitute biomarkers for cancer diagnosis and therapy. However, the specific function of miR‐9 in hepatocellular carcinoma (HCC) remains unclear, and the mechanisms that underlie HCC are incompletely understood. Here, we report that miR‐9 expression was significantly decreased in clinical tumor tissue samples, as well as in a cohort of HCC cell lines. In addition, it was demonstrated that overexpression of miR‐9 suppressed the proliferative and migratory capacity of HCC cells and impaired cell cycle progression. Furthermore, high mobility group AT‐hook 2 (HMGA2) was verified as a downstream target gene of miR‐9 using a luciferase reporter assay. Quantitative RT‐PCR and western blotting implicated HMGA2 in the miR‐9‐mediated reduction of HCC cell growth. In vivo, transfection with miR‐9 mimics down‐regulated the expression of HMGA2, thus leading to a dramatic reduction in tumor growth in a mouse xenograft model. These results suggest that miR‐9 may exert critical antitumor effects on HCC by directly targeting HMGA2, and the miR9/HMGA2 signaling pathway may be of use for the diagnosis and prognosis of patients with HCC.